World fisheries and aquaculture : (Food and Agriculture Organization of the United Nations, 2005)
Fisheries and related industries provide a livelihood for millions of people worldwide, and contribute significantly to world food security and international trade. This CD-ROM covers all aspects of fisheries and aquaculture, including information on development, ecosystems, More...governance, research, resources, statistics, technology and trade. It identifies the broad range of policy and other strategic issues affecting fisheries and considers the outlook for the future. It contains links to other documents and web sites; a glossary of terms related to responsible fisheries development; fact sheets on species, stocks, vessels, fishing gears and methods; and a range of illustrations, graphs and maps